Physical Activity Levels and Social Cognitive Processes among Adolescents - Atikah Rahayu; Sumaryanti Sumaryanti; Novita Intan Arovah (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2022)
This study aimed to study the correlation between physical activity level and social-cognitive process based on gender among adolescents. This study carried out a cross-sectional survey involving 94 adolescents in the Special Region of Yogyakarta, Indonesia (54.3% male, average 14±3 years). Physical activity level was assessed using the Physical Activity Questionnaire-Adolescent Questionnaire (PAQ-A). Social cognitive processes (including self-efficacy, outcome expectation, and self-regulation) were assessed using the Self-Efficacy for Exercise, the Multidimensional Outcome Expectations for Exercise, and the Self-Regulation Scales. Mann-Whitney test was used to compare physical activity levels and social-cognitive processes between males and females. Spearman correlation test was used to assess the association between physical activity level and social-cognitive process based on gender. The results of the study indicated no differences in the physical activity levels between male and female adolescents. Self-efficacy and outcome expectation did not correlate with physical activity level. In contrast, self-regulation was correlated with physical activity in male (r=0.279, p=0.048) and female (r=0.444, p=0.003) adolescents. The results indicate that self-regulation is the most important social-cognitive process determining physical activity level. For this reason, improving self-regulation skills is vital to promote physical activity levels among adolescents.